The Role of Education in Promoting Environmental Sustainability (College of Basic Education Research Journal, 2026)
The current research aimed to identify the role of educational institutions in promoting environmental sustainability. The researchers used the descriptive approach and developed a tool to measure environmental sustainability consisting of (20) items. The apparent validity of the questionnaire was confirmed after it was presented to a panel of arbitrators specializing in educational and psychological sciences. The psychometric properties were verified and the discriminatory power of the questionnaire items was calculated The stability sample consisted of (20) male and female teachers to determine the psychometric properties of the questionnaire. It was calculated using the Cronbach’s alpha method, which reached (0.82). As for the research sample, it consisted of (30) male and female teachers distributed among a number of primary schools. The data were processed statistically using the statistical package (SPSS). Based on the percentage weights and weighted means, the results showed that educational institutions play an acceptable role in promoting environmental sustainability. Based on the results, the researchers presented a number of recommendations, including: Emphasis on educational institutions by education directorates in order to promote environmental sustainability among learners. The researchers also presented a number of proposals for future research, including: The impact of using digital games in teaching environmental sustainability to primary school students.
Keywords: educational institutions; environmental sustainability